Effect of ankle taping on angle and force matching and strength of the plantar-flexors - Hopper, Diana; Grisbrook, Tiffany; Finucane, M.; Nosaka, K. (Elsevier, 2014)
Objective: Investigate the effect of ankle taping on plantar-flexion strength, angle matching and force matching. Design: Single group, repeated measures.Setting: Laboratory of an educational institutionParticipants: Twenty uninjured females (22.9 ± 3.6 years).Main Outcome Measures: Tape was applied to the ankle using a conventional hindfoot technique. Angle and force matching, and plantar-flexor strength were assessed using the purpose built dual ankle dynamometer, and measures were taken prior to and following taping. Angle matching was assessed passively and actively at 10, 15 and 20º of plantar-flexion. Participants were required to match the angle of the reference leg with the contralateral leg. Force matching was assessed at 10º of plantar-flexion and participants matched the torque of the reference leg with the contralateral leg.Results: Taping had no effect on absolute errors during active or passive angle matching. Regardless of taping, the ankle angle tested had a significant effect on passive angle matching (p<0.001); subjects were most accurate at matching a plantar-flexion angle of 20º. Ankle taping had no effect on force matching. Taping significantly improved peak plantar-flexion strength by 20% (p=0.028).Conclusion: Ankle taping has little effect on contralateral force and angle matching, but it can enhance peak plantar-flexion strength.